2023
DOI: 10.3390/jcm12062088
|View full text |Cite
|
Sign up to set email alerts
|

Intervortex Venous Anastomosis in the Macula in Central Serous Chorioretinopathy Imaged by En Face Optical Coherence Tomography

Abstract: Purpose: To assess the presence of macular intervortex venous anastomosis in central serous chorioretinopathy (CSCR) patients using en face optical coherence tomography (EF-OCT). Methods: A cross-sectional study where EF-OCT 6 × 6 and 12 × 12 mm macular scans of patients with unilateral chronic CSCR were evaluated for anastomosis between vortex vein systems in the central macula. The presence of prominent anastomoses was defined as a connection with a diameter ≥150 µm between the inferotemporal and superotempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Additionally, the anatomical location of the PED at the upper margin of the neurosensory detachment suggests that gravitational force contributed to the inferior accumulation of SRF. Furthermore, our patient had a pachyvessel beneath the PED and subretinal hyperreflective material surrounding the PED, both of which are also linked to the area of leakage in CSC [1,22,23]. Therefore, considering all indirect indicators of leakage, some CSC patients may not require angiography before FLP treatment, streamlining the treatment planning process.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, the anatomical location of the PED at the upper margin of the neurosensory detachment suggests that gravitational force contributed to the inferior accumulation of SRF. Furthermore, our patient had a pachyvessel beneath the PED and subretinal hyperreflective material surrounding the PED, both of which are also linked to the area of leakage in CSC [1,22,23]. Therefore, considering all indirect indicators of leakage, some CSC patients may not require angiography before FLP treatment, streamlining the treatment planning process.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, healthy patients can often show a relatively thick choroid without any pathological changes (Ikuno et al, 2010), while CVH is rarely found in healthy controls, thus making it a more specific sign of the disease (Bacci et al, 2022). The same holds true for other signs of venous overload such as intervortex venous anastomoses, which were observed in between 35% (Bacci et al, 2022) and 58% (Fernández-Vigo et al, 2023) of healthy controls and can thus not be regarded a pathologic sign only observed in diseases that are part of the pachychoroid spectrum (Funatsu et al, 2022;Sonoda et al, 2021). Based on these results, CVH appears to be a more meaningful diagnostic feature of CSC than either a thickened choroid or signs of venous overload.…”
Section: Choroidal Hyperpermeability Pattern Based On Ultra-widefield...mentioning
confidence: 99%
“…Although generally symmetrical, various diseases develop unevenly in the eyes of a given patient, e.g., age-related macular degeneration (AMD) [ 8 , 9 ] and glaucoma [ 10 ]. There are also differences between the eyes in the central serous chorioretinopathy (CSCR) [ 11 ] and myopia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%